Partial Least Square Method For Modelling Ergonomic Risks Factors On Express Bus Accidents In The East Coast Of Peninsular West Malaysia - Yusof, Hashim; Zahari, Taha (2015)
Public, stake holders and authorities in Malaysian government show great concern towards high numbers of passenger’s injuries and passengers fatalities in express bus accident. This paper studies the underlying factors involved in determining ergonomics risk factors towards human error as the reasons in express bus accidents in order to develop an integrated analytical framework. Reliable information about drivers towards bus accident should lead to the design of strategies intended to make the public feel safe in public transport services. In addition there is an analysis of ergonomics risk factors to determine highly ergonomic risk factors which led to accidents. The research was performed in east coast of peninsular Malaysia using variance-based structural equation modeling namely the Partial Least Squares (PLS) regression techniques. A questionnaire survey was carried out at random among 65 express bus drivers operating from the city of Kuantan in Pahang and among 49 express bus drivers operating from the city of Kuala Terengganu in Terengganu to all towns in the east coast of peninsular west Malaysia. The ergonomic risks factors questionnaire is based on demographic information, occupational information, organizational safety climate, ergonomic workplace, physiological factors, stress at workplace, physical fatigue and near miss accidents. The correlation and significant values between latent constructs (near miss accident) were analyzed using SEM SmartPLS, 3M. The finding shows that the correlated ergonomic risks factors (occupational information, t=2.04, stress at workplace, t = 2.81, physiological factor, t=2.08) are significant to physical fatigue and as the mediator to near miss accident at t = 2.14 at p<0.05and T-statistics, t>1.96. The results shows that the effects of physical fatigue due to ergonomic risks factors influence the human error as the reasons in express bus accidents.